2012
DOI: 10.1080/00207594.2012.682063
|View full text |Cite
|
Sign up to set email alerts
|

Validity evidence for the situational judgment test paradigm in emotional intelligence measurement

Abstract: To date, various measurement approaches have been proposed to assess emotional intelligence (EI). Recently, two new EI tests have been developed based on the situational judgment test (SJT) paradigm: the Situational Test of Emotional Understanding (STEU) and the Situational Test of Emotion Management (STEM). Initial attempts have been made to examine the construct-related validity of these new tests; we extend these findings by placing the tests in a broad nomological network. To this end, 850 undergraduate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
4
53
0
3
Order By: Relevance
“…MacCann and Roberts (2008) .13, .17, .17, .18, and .42;Austin, 2010;Ferguson & Austin, 2010;Libbrecht & Lievens, 2012;MacCann et al, 2011;Vonk et al, 2015) and in tone of voice (r = .27; MacCann et al, 2011).…”
Section: Emotion Perception and Emotion Regulationmentioning
confidence: 98%
See 3 more Smart Citations
“…MacCann and Roberts (2008) .13, .17, .17, .18, and .42;Austin, 2010;Ferguson & Austin, 2010;Libbrecht & Lievens, 2012;MacCann et al, 2011;Vonk et al, 2015) and in tone of voice (r = .27; MacCann et al, 2011).…”
Section: Emotion Perception and Emotion Regulationmentioning
confidence: 98%
“…Possible responses to each scenario were identified from a second sample, and the final responses were scored according to expert judgment as to the effect of the regulation strategy (where later research showed that the experts generally endorsed regulation strategies representing situation modification or cognitive change; Allen, Rahman, Weissman, MacCann, & Roberts, ). Like the STEU, Situational Measure of Emotion Management scores correlate positively with the perception of emotion in both faces ( r = .07, .13, .17, .17, .18, and .42; Austin, ; Ferguson & Austin, ; Libbrecht & Lievens, ; MacCann et al, ; Vonk et al, ) and in tone of voice ( r = .27; MacCann et al, ).…”
Section: Do the Narrow Abilities Of Ei Converge?mentioning
confidence: 99%
See 2 more Smart Citations
“…Development of the STEM used critical incidents interviews for the item and response generation and a group of experts for the scoring key development (for a detailed description, see . Available validity evidence for these new SJT-based EI tests is promising (e.g., Burrus et al, 2012;Libbrecht & Lievens, 2012;Libbrecht et al, 2014), though ongoing research continues to be directed at improving the design of these measures and underlying scoring models (see e.g., Allen, Weissman, Hellwig, MacCann, & Roberts, 2014;Allen, Rahman, Weissman, MacCann, & Roberts, 2015).…”
mentioning
confidence: 99%